2012
DOI: 10.1007/s10336-012-0842-2
|View full text |Cite
|
Sign up to set email alerts
|

Standing out from the crowd: are patagial wing tags a potential predator attraction for harriers (Circus spp.)?

Abstract: Wing tags have been used on many bird species to facilitate individual recognition, although tags are not only conspicuous for humans but may also attract the attention of potential predators. During a Peregrine Falcon monitoring program (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) we collected prey remains from the nests of 37 peregrine territories in the Basque Country, Northern Spain. We identified 3127 prey items representing 132 bird species. In the 2009 breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In Gyrfalcons fitted with backpack transmitters, preening frequency increased after deployment and persisted for several weeks of observation, suggesting that the birds failed to adjust rapidly to the attachment of radio transmitters (Booms et al 2011) We found no evidence that the attachment of patagial tags influenced breeding return rates of Sakers, nor did we detect any adverse effect on breeding behaviour. The effects of using patagial tags can vary according to species (Kochert et al 1983, Calvo & Furness 1992, Varland et al 2007, Trefry et al 2013 with some studies reporting little or no adverse impact of patagial tags (Smallwood & Natale 1998, Martin & Major 2010, Sergio et al 2015, whereas others have reported increased mortality due to predation (Saunders 1988, Zuberogoitia et al 2012, sub-lethal effects on breeding ecology (Jackson 1982, Bustnes & Erikstad 1990, reduced nesting success (Trefry et al 2013), physical effects such as feather wear and/or skin abrasion (Green et al 2004) and behavioural impacts on hunting efficiency (Sherrod et al 1981). The fact that five Sakers removed their patagial tags indicates that the markers were at least an irritation and possibly caused discomfort for the birds; removal of patagial tags has also been reported for Prairie Falcons (Kochert et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In Gyrfalcons fitted with backpack transmitters, preening frequency increased after deployment and persisted for several weeks of observation, suggesting that the birds failed to adjust rapidly to the attachment of radio transmitters (Booms et al 2011) We found no evidence that the attachment of patagial tags influenced breeding return rates of Sakers, nor did we detect any adverse effect on breeding behaviour. The effects of using patagial tags can vary according to species (Kochert et al 1983, Calvo & Furness 1992, Varland et al 2007, Trefry et al 2013 with some studies reporting little or no adverse impact of patagial tags (Smallwood & Natale 1998, Martin & Major 2010, Sergio et al 2015, whereas others have reported increased mortality due to predation (Saunders 1988, Zuberogoitia et al 2012, sub-lethal effects on breeding ecology (Jackson 1982, Bustnes & Erikstad 1990, reduced nesting success (Trefry et al 2013), physical effects such as feather wear and/or skin abrasion (Green et al 2004) and behavioural impacts on hunting efficiency (Sherrod et al 1981). The fact that five Sakers removed their patagial tags indicates that the markers were at least an irritation and possibly caused discomfort for the birds; removal of patagial tags has also been reported for Prairie Falcons (Kochert et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found adverse effects from patagial tags on bird survival (Zuberogoitia et al 2012), behaviour (Brua 1998), and nesting success (Trefry et al 2013), but studies on other species (Martin and Major 2010), including New and Old World vultures, found no measureable impacts on these larger birds (Wallace et al 1980, Sweeny et al 1985. Botha (2007) …”
Section: Discussionmentioning
confidence: 99%
“…Patagial tags have been extensively used as markers in the last decades and have played an important role in behavioural studies. However, several studies confirmed adverse effects of patagial tags related to behaviour, nesting success and survival [18][19][20]. Studies on vultures, suggested that patagial tags might affect the aerodynamics of flight by impacting lift [21], which could negatively affect the energetic cost of flight.…”
Section: Introductionmentioning
confidence: 99%